A status update on Southern Hemisphere Meteoroid Measurements with SAAMER - Janches, Diego (2019)
Hypervelocity meteoroid impacts are a risk to spacecraft operations. Mitigation of the meteoroid impact risk can be accomplished by implementing spacecraft designs that minimize the threat to critical systems, operational changes to the spacecraft orientation during mission operations, or a combination of both. Knowledge of the meteoroid threat in terms of mass-dependent flux (both rate and direction) is required in order to best implement the mitigation strategies. NASA’s Meteoroid Environment Office (MEO) assesses the risk posed to space assets by naturally occurring meteoroids, either from the sporadic background or meteors showers. Historically, most models used are based on monitoring the meteoroid environment in the Northern Hemisphere and only partially the Southern Hemisphere, leaving some potential threats without means to be catalogued. To address this gap, an effort to upgrade an existing radar facility in Southern Argentina is underway in order to develop the needed capability to provide the required data from the Southern Hemisphere.